The Mediators Role Of Organizational Behavior And Human Resource Management On The Association Of Shared Leadership And Job Performance In Almadar Aljadid Company. Libya - Mohamed RA K Badrani
Shared leadership is a type of leadership that has shown its importance in achieving organizational goals in many developing countries. It can contribute effectively to overcoming the challenges and difficulties facing human resource managers, especially with the increasing global and domestic competition between organizations sharing the same business operations. The purpose of this study is to investigate the effect of shared leadership on job performance and the mediating role of organizational behavior and human resource management in the relationship between shared leadership and job performance. This study aims to fill the gap in the application a of shared leadership style in Libya and its influence on job performance, to archive this aim, a quantitative methodology and structural equation modeling (SEM) were used to test the developed hypotheses and model fit. Stratified sampling was used to collect data and questionnaire survey was sent to 385 respondents in the Al-Madar Aljadid Company in Libya. The result of the study show that shared leadership exerts a positive influence on job performance. The study also shows that organizational behavior and human resource management mediate the relationship between shared leadership and job performance. Theoretically, this study enhances the knowledge on job performance by adding to the list of antecedents and the outcomes of shared leadership. From the managerial perspective, the study suggests that managers should invest more to improve their shared leadership style. Furthermore, the managers should study special modules on leadership that can develop their understanding of company and management operations. These finding call for further reflection on job performance through an in- depth study on employees of Libyan companies.